A Case of Rare Complication of Inguinal Parietoplasty according to Lichtenstein: Entero Cutaneous Fistula - K. B. Kouakou; K. I. Anzoua; M. Traore; B. K. I. Leh; A. B. N’Dri; A. S. Ekra; B. A. Kouakou; R. Lebeau; B. Diané (Case Reports in Surgery)
Lichtenstein intervention is currently the classic model of the regulated treatment of inguinal hernias by direct local approach. This “tension-free” technique satisfies both patients and practitioners. However, it does not often evade severe complications of parietal surgery. The authors report their treatment experience in rural Africa of a late enterocutaneous fistula which aggravated an inguinal hernia repair according to the Lichtenstein procedure. Physiopathology, diagnosis, and treatment of that disease are analyzed in the light of literature.